2000
DOI: 10.1517/13543776.10.8.1245
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological approaches to the treatment of diabetic complications

Abstract: Diabetes is often accompanied by several long-term complications such as neuropathy, nephropathy, retinopathy, cataract and angiopathy; their occurrence has been linked to the modification of the physiological levels of glycaemia. Several interrelated metabolic pathways have been implicated in the toxic effects of glucose; the polyol pathways was one of the first considered. However, while in diabetic animal models the inhibitors of aldose reductase (ALR2, the first enzyme of this pathway) seem to be active, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
70
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 72 publications
0
70
0
2
Order By: Relevance
“…A variety of ARIs have been reported; however, in clinical studies, many of them have exhibited low efficacy or a narrow spectrum of tissue activity, generally because of unfavorable pharmacokinetics, or have proved to produce toxic side-effects. At present, epalrestat is the only ARI available on the market [10][11][12]. Literature reveals that in the last few years, numerous 5-arylidene-2,4-thiazolidinediones derivatives produced appreciable ALR inhibition [13,14], but their effectiveness generally decreases in vivo, probably due to their poor penetrability to key target tissues, in particular, peripheral nerves [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of ARIs have been reported; however, in clinical studies, many of them have exhibited low efficacy or a narrow spectrum of tissue activity, generally because of unfavorable pharmacokinetics, or have proved to produce toxic side-effects. At present, epalrestat is the only ARI available on the market [10][11][12]. Literature reveals that in the last few years, numerous 5-arylidene-2,4-thiazolidinediones derivatives produced appreciable ALR inhibition [13,14], but their effectiveness generally decreases in vivo, probably due to their poor penetrability to key target tissues, in particular, peripheral nerves [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Besides, it was reported that some 2,4-TZDs have been used as antihyperglycemic 6 and aldose reductase (AR) inhibitory agents with dual activity. 7 There is a great interest in 2,4-TZD derivatives as aldose reductase inhibitors (ARIs), 7,8 since they can be viewed as hydantoin bioisosters potentially free of the hypersensitivity reactions which are linked to the presence of the hydantoin system.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last three decades numerous ALR2 inhibitors (ARIs) have been identified, most of which belong to the carboxylic acids (such as zopolrestat, ponalrestat, epalrestat) and hydantoins (such as sorbinil) classes of compounds. [1][2][3][4][8][9][10][11] Nevertheless, many of them have shown to be clinically inadequate because of adverse pharmacokinetics or toxic side-effects. [10] At present, epalrestat is the only ARI available on the market.…”
Section: Introductionmentioning
confidence: 99%